SELF-MEDICATION AMONG MEDICAL STUDENTS DURING COVID-19 PANDEMIC: A CROSS SECTIONAL STUDY - Razzak, Sadaf; Noor, Maha; Abbas, Zainub; Iqbal Paracha, Malaika; Parvez, Rabab (Journal of Postgraduate Medical Institute, 2024)
Objectives: To find out the frequency of self-medication among medical students, specifically during the onset ofbCOVID-19 symptoms or after a positive test. Methodology: The present study was conducted on medical students of a public university with the cross sectionalbtype of research. This study was conducted from July 2021 to September 2021. With a sample size of 358bcalculated via Open Epi, data was collected using an online questionnaire via Google Forms after obtaining ethicalbapproval. Demographic details and responses were gathered anonymously. All data were entered into SPSS versionb20 for analysis purposes. Data were presented in the form of proportion and means with standard deviation. Results: Over-all 363 students were registered in the study with 320 (88.2%) respondents being female. Mean age of the study cases were 21±2.5 years. Among study cases, 166 (45.7%) students, self-medicated with widely used medicines. Out of these 166, analgesics/antipyretics were the most frequently used class of medication (n=79, 47.59%), followed by antacids (n=35, 21.08%), antibiotics (n=28; 16.86%), and anti-allergic medications (n=24, 14.45%). The common antibiotics used in self-medication among the 28, were amoxicillin (n=11 39.28%) and azithromycin (n=8, 28.57%). Conclusion: Nearly half of the participants self-medicated, with analgesics/antipyretics being the most commonly used medications. Among antibiotics, amoxicillin and azithromycin were prominently used antibiotics.